KOLOKASI DALAM BAHASA MUNA - Siti Fatinah (Balai Bahasa Sulawesi Tengah, 2013)
The language of Muna as the spoken language in its regional, has its distinguished characteristics and patterns in words combination. This paper’s aim is about the description of collocation pattern in Muna language. Method applied in the collecting data is the listening, speaking, and introspecting method. The technique applied are listening with conversation, listening without conversation, and recording technique. During analysis process, the method applied are intralingual error analysis with the comparison and contrast technique. After the analysis, the data is presented by formal and informal method. The result shows that Muna language consist id four collocations pattern, which are (1) collocation of group I [N + Adj], consists of 8 types that is (a) N [+human, +concrete, +countable, dan +soul] with Adj [+situation]; (b) N [+human, +concrete, +countable] with Adj [+character or +action]; (c) N [-human, +concrete, +countable, dan -soul] with Adj [+situation]; (d) N [-human, +concrete, +countable, -soul, and +part of body] with Adj [+situation]; (e) N [-human, +concrete, +countable, -soul, and +part of body] with Adj [+situation]; (f) N [-human, +concrete, +countable, -soul, dan +part of body] with Adj [+situation]; (g) N [-human, +concrete, +countable, and -soul] with Adj [+size]; and (h) N [-human, +concrete, -countable, and -soul] with Adj [+size]; (2) collocation of group II is noun and adjective [N + Adj], which are consists of three types: (a) Adj [+situation] with N [-human, +concrete, +countable, -soul]; (b) Adj [+quality] with N [-human, -concrete, -countable, -soul]; and (c) Adj [+size/situation] with N [-human, -concrete, -countable, -soul]; (3) collocation of group III noun and verba [N + V]; and (4) collocation of group IV is noun and noun [N + N], consists of two types (a) N [+human, +concrete, +countable, and +soul] with N [+human, +concrete, +countable, and +soul]; (b) N [+human, +concrete, +countable, and +soul] with N [-human, +concrete, +countable, and -soul].